Evaluation of anti-Wnt/β-catenin signaling agents by pGL4-TOP transfected stable cells with a luciferase reporter system - K.A. Chuang; C.H. Lieu; W.J. Tsai; M.H. Wu; Y.C. Chen; J.F. Liao; C.C. Wang; Y.C. Kuo (Brazilian Journal of Medical and Biological Research, 2010)
Refractory and relapsed leukemia is a major problem during cancer therapy, which is due to the aberrant activation of Wnt/β-catenin signaling pathway. Activation of this pathway is promoted by wingless (Wnt) proteins and induces co-activator β-catenin binding to lymphoid enhancer factor (LEF)/T-cell factor protein (TCF). To provide a convenient system for the screening of anti-Wnt/β-catenin agents, we designed a bi-functional pGL4-TOP reporter plasmid that contained 3X β-catenin/LEF/TCF binding sites and a selectable marker. After transfection and hygromycin B selection, HEK 293-TOP and Jurkat-TOP stable clones were established. The luciferase activity in the stable clone was enhanced by the recombinant Wnt-3A (rWnt-3A; 100-400 ng/mL) and GSK3β inhibitor (2’Z,3’E)-6-bromoindirubin-3’-oxime (BIO; 5 µM) but was inhibited by aspirin (5 mM). Using this reporter model, we found that norcantharidin (NCTD; 100 µM) reduced 80% of rWnt-3A-induced luciferase activity. Furthermore, 50 µM NCTD inhibited 38% of BIO-induced luciferase activity in Jurkat-TOP stable cells. Employing ³H-thymidine uptake assay and Western blot analysis, we confirmed that NCTD (50 µM) significantly inhibited proliferation of Jurkat cells by 64%, which are the dominant β-catenin signaling cells and decreased β-catenin protein in a concentration-dependent manner. Thus, we established a stable HEK 293-TOP clone and successfully used it to identify the Wnt/β-catenin signaling inhibitor NCTD.